(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
The four Amphiastrea species from the Early Aptian of the Monti d’Ocre area described as new by Prever (1909) are revised on the basis of the type material. One species - Amphiastrea paronai - remains in this genus. Another - Amphiastrea delorenzoi - cannot be assigned to any genus. The remaining two species belong to the new genus Hexamphiastrea, which differs from all amphiastreid genera by its regular hexameral septal symmetry. Amphiaulastrea suprema Morycowa & Marcopoulou-Diacantoni, 1997 from the Early Aptian of Greece is designated as the type species. The new genus is only known from the Early Aptian of Italy and Central Greece.